Disasters in History and the History of Disaster: Some Key Issues - Angelli F. Tugado, Filomeno V. (Archīum Ateneo, 2016)
This concludingarticle identifies some of the salient themes that run across thearticles in this special double issue on “Disasters in History.” The common themes include (a) disasters as catalysts of different types of change in society, the state, and science; (b) the relationship between disasters and social inequality; (c) the attribution to nature of the ability as an actor in history, which raises questions about how to conceptualize nature’s agency; (d) disasters as constituting a specific type of modern discourse; and (e) the limitations to the geographical frame of the national discourse on disasters.Keywords: disasters • historiography • social analysis • cosmology • modernity